Fabrication and Evaluating Cellulose Acetate Flat-Sheet FO Membranes with Ionic-Liquid ([HBet][Tf₂N]) and Inorganic (NaCl, MgCl₂) Draw Solutions (Comprehensive Journal of Science, 2025)
Forward osmosis (FO) has emerged as a highly attractive separation process for water desalination due to its reliance on natural osmotic pressure gradients rather than high external hydraulic pressures. In FO, water molecules spontaneously diffuse from a dilute feed solution toward a concentrated draw solution through a semi-permeable membrane that selectively permits water transport while rejecting solutes. In the present investigation, cellulose acetate (CA) flat-sheet membranes were prepared with two different polymer loadings (20 wt.% and 25 wt.%) in order to assess the relationship between membrane structure and FO performance. Experimental results revealed that lowering the polymer concentration significantly enhanced water flux, albeit at the expense of reduced solute rejection, underscoring the classical permeability–selectivity trade-off. Furthermore, the influence of thermal conditioning through a two-step heat treatment (20 min at 60 °C and 90 °C) was systematically analyzed. The untreated CA membrane achieved the highest water flux of 1.48 L·m⁻²·h⁻¹, in contrast to 1.254 L·m⁻²·h⁻¹ and 1.006 L·m⁻²·h⁻¹ for membranes subjected to 60 °C and 90 °C treatment, respectively, highlighting the flux decline induced by thermal densification of the polymer matrix. Remarkably, the CA-0 membrane exhibited superior water permeation when paired with the UCST ionic liquid ([Hbet][Tf₂N]) as the draw solution. Within 30 seconds, approximately 7.0 g of feed water was transported across the membrane, outperforming conventional inorganic salts such as NaCl (6.33 g) and MgCl₂ (4.12 g) under identical operating conditions. These findings confirm that the UCST ionic liquid offers a stronger osmotic driving force, thereby achieving superior flux performance and demonstrating its potential as a next-generation draw agent for FO desalination.
Keywords: Cellulose acetate (CA); Forward osmosis (FO); Ionic liquid ([Hbet][Tf₂N]); Heat treatment.